2020
DOI: 10.1002/aoc.6087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized pyrimidouracils by ruthenium‐catalyzed oxidative insertion of (hetero)aryl methanols into N‐uracil amidines

Abstract: A dehydrogenative coupling of N‐uracil amidines with (hetero)aryl methanols has been developed, allowing for the facile synthesis of a broad range of structurally diverse pyrimidouracils. By applying [RuCl2(p‐cymene)]2/Cs2CO3 as an efficient catalytic system, the easily available, cheap (hetero)aryl methanols were firstly employed for oxidative insertion/CH amination into the N‐uracil amidines, providing highly functionalized pyrimido[4,5‐d]pyrimidine‐2,4‐diones. Due to the better stability of alcohols than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…From this elegant idea, recently we reported a dehydrogenative coupling between N-uracil amidines (88) and (hetero)aryl methanols (91) for the synthesis of structurally diverse pyrimidouracils. [90] The oxidative insertions of alcohols into the N-uracil amidines were achieved by applying 2.5 mol% of [RuCl 2 (p-cymene)] 2 as a catalyst and Cs 2 CO 3 as a base in DMSO at 110 °C (Scheme 28). A variety of functionalized pyrimido[4,5-d]pyrimidine-2,4-diones (89) were obtained in high yields utilizing commercially available and cheap (hetero)aryl methanols.…”
Section: Synthesis Of Pyrimidopyrimides Using N-uracil Amidines As St...mentioning
confidence: 99%
“…From this elegant idea, recently we reported a dehydrogenative coupling between N-uracil amidines (88) and (hetero)aryl methanols (91) for the synthesis of structurally diverse pyrimidouracils. [90] The oxidative insertions of alcohols into the N-uracil amidines were achieved by applying 2.5 mol% of [RuCl 2 (p-cymene)] 2 as a catalyst and Cs 2 CO 3 as a base in DMSO at 110 °C (Scheme 28). A variety of functionalized pyrimido[4,5-d]pyrimidine-2,4-diones (89) were obtained in high yields utilizing commercially available and cheap (hetero)aryl methanols.…”
Section: Synthesis Of Pyrimidopyrimides Using N-uracil Amidines As St...mentioning
confidence: 99%
“…In order to alleviate these shortcomings, we have developed another synthetic protocol for the preparation of 1,3,5,7tetrasubstituted pyrimido[4,5-d]pyrimidines via TBHP-mediated direct oxidative coupling of N-uracil amidines and under metal-free conditions [35]. Very recently, we also observed that pyrimidouracils synthesis could also be accomplished by ruthenium catalyzed oxidative insertion of aryl methanols into N-uracil amidines [36]. In continuation of our efforts towards the synthesis of nitrogen heterocycles, an efficient synthetic procedure for the synthesis of pyrimidouracils via PhI(OAc)2 mediated oxidation insertion of methylarenes into N-uracil amidines has been developed.…”
Section: Introductionmentioning
confidence: 99%